Improved process intermediate stability through the identification and elimination of reactive glycation residues – a monoclonal antibody case study. Issue 6 (1st June 2022) - Bosley, Allen; Cook, Kimberly; Lin, Shihua; Robbins, David
ABSTRACT: The manufacturing of therapeutic biologics can result in a heterogeneous population of charge variants, encompassing many quality attributes which could impact activity and pharmacokinetics. Monitoring the relative abundance of these charge variants to demonstrate process consistency is an expectation of regulatory agencies. Control of the relative abundance of charge variants is also necessary to ensure product comparability across the product lifecycle. We have observed a significant shift in the relative abundance of charged species, as measured by capillary isoelectric focusing, during clarified cell culture fluid holds for several monoclonal antibodies. This lack of stability requires that the hold time for this process intermediate be significantly curtailed, eliminating manufacturing flexibility. We have identified the cause of this shift in relative abundance of charged species as changes in glycation levels, focused predominantly on three conserved, solvent accessible, lysine residues. Mutants of a model protein were generated that show increased charge state stability can be gained by eliminating these reactive lysines. Further, characterization studies were conducted on these mutants to determine the impact to biological activity and stability of the molecule, with no detrimental effects observed. Incorporating this knowledge into the assessments of candidate drugs could allow for the selection of molecules less susceptible to this product degradation pathway, allowing for greater manufacturing flexibility. This process of identifying and removing reactive lysine residues could be useful in the design of drug candidates with improved charge state stability, across a range of modalities. ABSTRACT: uf0001